THE IMPLEMENTATION OF CURRICULUM 2013 FOR PHYSICAL EDUCATION, SPORT AND HEALT OF JUNIOR HIGHSCHOOL IN SAMARINDA - Muhammad Sukron Fauzi (Acitya: Journal of Teaching and Education, 2019)
This study aims to determining the Implementation of Curriculum 2013 in the scope of content standard, process standar, and assessment standar for Physical Education, Sport, and Health of junior high school. This study was an evaluation research based on mix method of deskriptif quantitative approach. The evaluation model was responsive that had an objective to find out the responses of teachers about the implementation of curriculum 2013. This study was taken place in Junior High School. The total of the population was 81 School and the sample used in this study were 20 school based on the proportionate stratified random sampling technique. The data collection instrument were quesionaire for teachers physical education sport and healt. The findings showed. The implementation of Curriculum 2013 in the scope of content standar was apropriate with the guidance of Curriculum 2013 with the percentation of responden’s response was 82,4%, The implementation of Curriculum 2013 in the scope of process standar was apropriate with the rules of Curriculum 2013 with the percentation of responden’s response was 82,8%, The implementation of Curriculum 2013 in the scope of assessment standar was apropriate with the guidance of Curriculum 2013 with the percentation of responden’s response was 80,4%. Conclusions are the implementation of the 2013 curriculum including content standards, process standards, and assessment standards for junior high schools in the city of Samarinda, which have run according to the format, guidelines and policies of the government regarding the implementation of the 2013 curriculum.